POTENSI PENERIMAAN PAJAK DARI TRANSAKSI ELEKTRONIK DI KABUPATEN SUBANG - Mei Shafarindah Hermawati; Fitri Cahyati; Indah Febriyanti; Inggit Aprilia; Widi Juwianti (Journal of Taxation Analysis and Review, 2021)
Taxes are a very impotant contributor to the administration and implementation of national development. With taxes, the state can prosper the people, carry out development and in order to achieve common interets. The study aims to test potential tax receipts from electronic transactions in Subang districts. The research method used is qualitative method using descriptive approach. This study uses qualitative approach with case study method. The data in the analysis is the results of interviews with 3 people, 1 person fiskus Subang tax revenue office (KPP) working in the general section, 1 academician SMK PGRI SUBANG, and 1 business person who uses the digital platform s.r.y shop. The result of the reseacrh are as follows: the potential of tax receipts in that the growing users of e-commerce will have a good impact on taxtion even that development can facilitate us in transacting with the use of internet for commercial activities can also help in transactions and the development becomes one of the potentials in tax receipts. Even KPP itself has a facility called tax intensive it becomes an effort to facilitate or encourage taxpayers to comply in carrying out their obligations. Keywords: Tax, Online transactions, Potential tax on online transactions